Factors that Influence the Effectiveness of Communication between Teachers and Deaf Students - Nuzuli, Ahmad Khairul (Jurnal Komunikasi Pendidikan, 2024)
Effective communication is an important requirement for all individuals, and everyone wants smooth and seamless interactions. However, persistent communication barriers are a common problem, even in communication contexts involving deaf students. The main objective of this research is to determine the inhibiting and supporting elements in the communication process between teachers and deaf students in the SLBN Sungai Banyak City. Using qualitative descriptive methods and a phenomenological approach, the findings of this research identify physical and semantic barriers as inhibiting factors, while clarity, accuracy, context awareness, and cultural considerations are supporting elements. This research is important because it can provide valuable guidance and recommendations for educators who want to understand communication challenges and improvements when interacting with their students.